(untitled) (Scientific journal of the Fergana State University, 2023)
The main form of training young athletes is training. Through the training system, a targeted pedagogical effect is achieved, the main sports, health-improving and educational tasks are solved. The system of sports exercises, presented in an interesting way, largely predetermines the success of training, sets young athletes in a hard-working mood and often sets the final goal of educational work in training. The main goal of training is not the fact that young athletes master one or another system of exercises, but to understand and master certain rules for developing certain patterns of mastering specific sports skills, which can "lose" any sporting situation. This article discusses the role of special training processes in organizing offensive actions of future basketball players. Theoretically and practically, attack tactics and the principles of teaching them to children are covered.